Transpondo procedimentos psicométricos para a área da educação com vistas à construção de exames escolares enquanto diagnóstico - Aquiles Augusto Maciel Pires (2019)
School exams perform a major role as a source of information used by teachers for the elaboration of diagnoses both of the domain of academic content and of the learning process of their students. In spite of this, the school has generally restricted the use of school exams for the purpose of success or failure of the students, underutilizing their diagnostic function. Diagnosing student’s knowledgement is an important of the activity of the teaching practice, since it allows the teacher to more effectively elaborate his/her pedagogical planning and intervention. In this sense, the role of school exams as a diagnostic of the student's knowledge and learning process is an aspect that should be emphasized. However, there are technical challenges to overcome so that school exams can be consistent diagnoses. Problems of validity and reliability, handling with the elaboration of questions, the relationship between the questions and the school domains to be checked, among other aspects, need to be considered. Taking into account the problematics pointed out, this Thesis seeks to contribute with the initiative of emphasizing the school exams as a diagnosis. Thus, this Thesis proposes the transposition of some knowledge of psychometrics the education field that allows to bring technical elements that subsidize the elaboration of school exams as a diagnosis. The first study of this Thesis problematizes and points out fundamental elements that would support the school exams as a diagnosis. In addition, this study identifies and describes three procedures for the preparation of school exams often used by teachers and which have made it difficult for the exams to present evidence of validity and reliability. At the same time as it discusses these procedures, this study presents alternative actions that teachers can use in order to avoid that exams elaborated by them present the problems above mentioned. The second study elaborates and presents a methodology that integrates in the same exam the verification of school domains and variables that predict academic performance. This methodology integrates the assessment of school domains with four metacognitive abilities: xii feeling-of-knowing, self-management, judgement and monitoring (error detection). Three fundamental properties that support the proposed methodology are reported. An application is showed. In summary, through these two studies, this Thesis presents, discusses and proposes actions that aim to make information from school exams not only more correct, from the point of view of validity and reliability, but also richer, by incorporating predictors of the academic performance. It is hoped that this thesis and the proposed actions will encourage teachers and the school to elaborate and emphasize school exams as a diagnosis.